Analysis of loose roll mark of hot-rolled pickling alloyed galvanized automobile sheet. Issue 1 (1st December 2022) - Zuo, Rong; Xiong, Taotao; Chen, Ming; Zhu, Bixue; Li, Liejun
Abstract: The loose coil mark of hot-rolled pickling alloyed galvanized automobile plate is one of the main defects affecting the quality of steel plates. In this paper, the composition of the loose coil mark and the coiling process parameters of the hot-rolled pickling galvanized sheet was analyzed. The results showed that the main reasons for the loose coil marks were insufficient friction between the coiler mandrel and the strip, and the coiling tension of the lead head was unstable. By increasing the lead rate of head coiling speed to 15 mpm and increasing the crimp tension limit, the loose coil marks of hot-rolled pickling alloyed galvanized automobile plate were significantly reduced, and the quality of the steel plate was significantly improved. The unqualified steel plate caused by the defect of plate loose coil marks was downgraded from 100 t/month to 15 t/month.